Sinorhizobium fredii HH103 nolR and nodD2 mutants gain capacity for infection thread invasion of Lotus japonicus Gifu and Lotus burttii. (20th March 2019) - Acosta‐Jurado, Sebastián; Rodríguez‐Navarro, Dulce‐Nombre; Kawaharada, Yasuyuki; Rodríguez‐Carvajal, Miguel A.; Gil‐Serrano, Antonio; Soria‐Díaz, María E.; Pérez‐Montaño, Francisco; Fernández‐Perea, Juan; Niu, Yanbo; Alias‐Villegas, Cynthia; Jiménez‐Guerrero, Irene; Navarro‐Gómez, Pilar; et al.
Summary: Sinorhizobium fredii HH103 Rif R, a broad‐host‐range rhizobial strain, forms ineffective nodules with Lotus japonicus but induces nitrogen‐fixing nodules in Lotus burttii roots that are infected by intercellular entry. Here we show that HH103 Rif R nolR or nodD2 mutants gain the ability to induce infection thread formation and to form nitrogen‐fixing nodules in L. japonicus Gifu. Microscopy studies showed that the mode of infection of L. burttii roots by the nodD2 and nolR mutants switched from intercellular entry to infection threads (ITs). In the presence of the isoflavone genistein, both mutants overproduced Nod‐factors. Transcriptomic analyses showed that, in the presence of Lotus japonicus Gifu root exudates, genes related to Nod factors production were overexpressed in both mutants in comparison to HH103 Rif R . Complementation of the nodD2 and nolR mutants provoked a decrease in Nod‐factor production, the incapacity to form nitrogen‐fixing nodules with L. japonicus Gifu and restored the intercellular way of infection in L. burttii . Thus, the capacity of S. fredii HH103 Rif R nodD2 and nolR mutants to infect L. burttii and L. japonicus Gifu by ITs and fix nitrogen L. japonicus Gifu might be correlated with Nod‐factor overproduction, although other bacterial symbiotic signals could also be involved.